Synthesis, biological evaluation and molecular docking study of pyrimidine based thiazolidinone derivatives as potential anti-urease and anti-cancer agents - Shoaib Khan; Hayat Ullah; Fazal Rahim; Rafaqat Hussain; Yousaf Khan; Muhammad Saleem Khan; Rashid Iqbal; Baber Ali; Mohammed Fahad Albeshr (Journal of Saudi Chemical Society, 2023)
Hybrid analogs containing molecules are always the choice of different synthetic researcher due to their diverse biological applications and significantly more efficient. Heterocyclic being a good inhibitors against varied disease are most commonly used in drug designing and development. The current study also addressed the synthesis of pyrimidine-based thiazolidinone derivatives (1–13) using stepwise processes and their structure was confirmed using various characterization techniques such as 1HNMR, 13CNMR, and HREI-MS. Furthermore, the biological significances of the synthesized scaffolds were also explored and proved to be as anti-urease and anti-cancer moieties. Their inhibitory potentials were determined using the minimum inhibitory concentration (MIC) in the presence of their standard drugs, Thiourea (IC50 = 8.20 ± 0.20 µM) and Tetrandrineb (IC50 = 12.30 ± 0.10 µM) respectively. Structure activity relationship (SAR) was established for all the synthesized scaffolds and compared their inhibitory potentials in which scaffolds 3 (IC50 = 2.30 ± 0.30 and 3.20 ± 0.50 µM), 6 (IC50 = 3.10 ± 0.20 and 6.20 ± 0.10 µM), 7 (IC50 = 3.20 ± 0.20 and 3.80 ± 0.30 µM) and 10 (IC50 = 4.20 ± 0.20 and 5.10 ± 0.30 µM) exhibited the most influential activity. These compounds were subsequently examined using molecular docking experiments, which evaluate the binding interaction of ligands with enzyme active sites.